Wheelchair User’s Satisfaction and its Impact on Physical Activity and Quality of Life in People with Spinal Cord Injury - Mehmood, Beenish; Ali, Iftikhar; Daud, Syeda Afsheen; Ilyas, Syed Muhammad (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2022)
Background Spinal cord injury (SCI) survivors rely greatly on assistive devices, spending around 9–11 hours daily in a wheelchair. It can act both as a barrier and facilitator, positively impacting their mobility, community participation, quality of life (QOL) and functional independence provided the device is satisfactory. However, there is a paucity of information on the level of user satisfication and its impact on the mobility and well being. Keeping in view the present study was conducted to determine the level of wheelchair user’s satisfaction and its impact on physical activity and QOL in SCI.Methods A cross sectional study with a sample of 130 was conducted at Paraplegic Center, Peshawar using “Quebec User Evaluation of Satisfaction with assistive Technology (QUEST)” for wheelchair user’s satisfaction, “Physical Activity Scale for Individuals with Physical Disabilities (PASIPD) for physical activity and World Health Organization Quality of Life (WHOQOL-BREF) for QOL.Results Mean age of the study participants was 32.48±11.96 years. The majority of the participants were males, with most of them being manual wheelchair users. Nearly 80% were regular users. The calculated mean for the QUEST was 3.23±0.51 while 24.49±27.66 for the PASIPD. For the WHOQOL-BREF the calculated median (IQR) in the environmental 56.00 (19.00) and psychological 56.00 (12.00) domain was highest followed by physical domain 50.00(19.00). No significant correlation between participant’s satisfaction level (for wheelchair), and PASIPD (rs=0.054, p=0.541) was observed. On the other hand significant positive correlation was found between physical (rs=0.394, p<0.001), social (rs=0.303, p<0.001) and environmental domain (rs=0.425, p<0.001) except psychological domain (rs=0.156, p=0.076) of QOL.Conclusion The majority of the participants showed moderate levels of satisfication and the impact was observed on the physical, social and environmental domains of QOL. Appropriate wheelchairs enhancing the QOL therefore special measures should be taken to customize the device to the body structure and needs of the customers as anything that can improve their lives even to a minor extent can prove very helpful.
Keywords: Wheelchair user’s satisfaction (QUEST); quality of life; physical activity; spinal cord injury; PASIPD; WHOQOL-BREF